2022
DOI: 10.1177/20499361221122481
|View full text |Cite
|
Sign up to set email alerts
|

When law and science part ways: the criminalization of breastfeeding by women living with HIV

Abstract: Stigma and discrimination are a constant reality for the 37.7 million people living with human immunodeficiency virus (HIV) around the globe. Fear over vertical transmission has fuelled HIV criminalization: laws that target people living with HIV for acts deemed to be a transmission risk. Research has now shown that many of these behaviours, including breastfeeding, pose an extremely low risk of transmission when people have proper medical care, access to treatment and open relationships with medical professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Such laws are often at odds with the best available science about HIV, including what we know about the low, negligible or non-existent possibility of transmission in circumstances that nonetheless still attract prosecution in many jurisdictions. 81 , 82 Multiple reviews of the literature have demonstrated that HIV criminalisation laws appear to have little impact in reducing sexual risk behaviours, while causing harm in multiple ways to people living with and communities affected by HIV, and more generally undermining an effective HIV response. 83–85 HIV criminalisation contributes to misinformation about HIV and its transmission, thereby further stigmatising people living with HIV and fostering social ostracism, discrimination and violence.…”
Section: Criminalising People Living With Hivmentioning
confidence: 99%
“…Such laws are often at odds with the best available science about HIV, including what we know about the low, negligible or non-existent possibility of transmission in circumstances that nonetheless still attract prosecution in many jurisdictions. 81 , 82 Multiple reviews of the literature have demonstrated that HIV criminalisation laws appear to have little impact in reducing sexual risk behaviours, while causing harm in multiple ways to people living with and communities affected by HIV, and more generally undermining an effective HIV response. 83–85 HIV criminalisation contributes to misinformation about HIV and its transmission, thereby further stigmatising people living with HIV and fostering social ostracism, discrimination and violence.…”
Section: Criminalising People Living With Hivmentioning
confidence: 99%